Zwrot kulturowy w badaniach onomastycznych - Lech-Kirstein, Danuta (Poznańskie Spotkania Językoznawcze, 2015)
In the recent years, a turn towards interdisciplinary research in which proper names are presentedas an interpretation of reality and a mirror of historical, political, social and cultural processes has been observed in onomastics. Names can reflect a popular vision of the world presenting its anthropocentric conceptualization reconstructed on the basis of knowledge, beliefs, valuation systems and cultural experiences of people. Thus the cultural analysis of onyms comprises notions of a linguistic image of the world, point of view, profiling, conceptualization and categorization of ideas, valuation, stereotype and prototype, connotation, metaphor and metonymy. Special attention is also paid to the secondary functions of proper names which, apart from indicating and identifying objects, can also perform metaphorical, expressive, ludic, pragmatic and marketing functions. The so-called cultural onomastics focuses on the study of proper names in this aspect. The analysis of onyms is shifted in it towards the creator and interpreter, presenting the manner of conceptualizing a selected fragment of reality in the categories of a consolidated mental pattern. Interdisciplinary research develops in many directions, making use of the methods and notions of such sciences as sociology, psychology, folk medicine, cognitivism, ethnology, folkloristics, anthropology, religious studies, neurology. Cultural onomastics concentrates on a variety of proper names belonging to the fields of anthroponymy, toponymy, media onymy and chrematonymy. Furthermore, the new research fields necessitate changes in the traditional methodology as well as consideration of a broad social and cultural context within a particular system of values.